An estimate of solar radiation over Bangladesh - HUSSAIN, M. H.; CHOWDHURY, S.A. (MAUSAM, 1990)
Globa1 solar radiation distribution over Bangladesh has been estimated with a modified Angstrom equation. Based on data for five; years at Dhaka, a regression formula has been derived for Bangladesh. This equation is then applied to sunshine and cloudiness data from 6 stations In Bangladesh for the computation of global solar radiation for the twelve months of a year. Spatial distribution of global solar radiation is found to be nearly uniform over the whole country. Global solar radiation is seen to be maximum exceeding 19.68 MJm-2day-l in March-April and minimum, less than 12.56 MJm-2 day-l In January. Values of outgoing long wave radiation for the twelve months of a year have been computed using Brunt’s empirical equation and net radiation values calculated with an assumed value of albedo. It is seen that the average short wave flux received by the country is less than 5860 MJm-2 year-1 while the average net radiation value is less than 4190 MJm-2 year-1.